Chicana Foundation 1995 - Workshop, San Jose City College, Tape 2 - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the workshop, Making the Most of Your College Education, presented by the Chicana-Latina Foundation. Held at San Jose City College. Including a video of an onboarding meeting for transfer students. Tape 2.